For anti-imperialist unity of the world youth : 8th assembly of WFDY - Schmal (World Federation of Democratic Youth, 1970)
Black and white poster; sphere representing the globe, wrapped in barbed wire Poster advertising assembly of the FMJD, held in Budapest, 26 October-4 November, 1970 PO-0208